Academic Stress Affects Smartphone Addiction in Nursing Student - Panma, Yuanita (STIKep PPNI Jawa Barat, 2022)
Aims: The development of information and communication technology today is very beneficial for public. Smartphones are cellular phones with many capabilities, ranging from resolution, features, to computing with various benefits especially for students. Smartphones are used in various ways including to obtain information, for financial transactions both shopping and work or for social media. Continuous use of smartphones in students can lead to smartphone addiction which can cause physical and psychological health problems. Purpose: To identified relationship between academic stress and smartphone addiction in nursing student. Methods: This study used cross sectional design with purposive sampling. There were 150 respondent who meet the inclusion criteria. The instruments used were the respondent characteristic questionnaire, the Smartphone Addiction Scale Short Version (SAS-SV) questionnaire, and the Student Life Stress Inventory (SLSI) questionnaire. Results: Majority respondents were female (90.7%), senior high school majoring was science (40%), second year of study (36.7%), not experienced smartphone addiction, experienced severe academic stress (54%), and mean of age was 19.67 year.In bivariate analysis there was a significant relationship between age (p = 0.048), year of study (p = 0.038) and academic stress (p = 0.035) with smartphone addiction.Smartphone addiction did not have a significant relationship with gender. Conclusion: A significant relationship were found between age, year of study, and academic stress with smartphone addiction. Suggestion: To prevent smartphone addiction in nursing student, academic stress should be reduced with develop educational programs for students to control the academic stress